B(C6F5)3‐Catalyzed Selective Chlorination of Hydrosilanes. (21st March 2017) - Chulsky, Karina; Dobrovetsky, Roman
Abstract: The chlorination of Si−H bonds often requires stoichiometric amounts of metal salts in conjunction with hazardous reagents, such as tin chlorides, Cl2, and CCl4 . The catalytic chlorination of silanes often involves the use of expensive transition‐metal catalysts. By a new simple, selective, and highly efficient catalytic metal‐free method for the chlorination of Si−H bonds, mono‐, di‐, and trihydrosilanes were selectively chlorinated in the presence of a catalytic amount of B(C6 F5 )3 or Et2 O⋅B(C6 F5 )3 and HCl with the release of H2 as a by‐product. The hydrides in di‐ and trihydrosilanes could be selectively chlorinated by HCl in a stepwise manner when Et2 O⋅B(C6 F5 )3 was used as the catalyst. A mechanism is proposed for these catalytic chlorination reactions on the basis of competition experiments and density functional theory (DFT) calculations.